Horticultural hybrid development of edible terrestrial orchids for verifiable sustainable trade - Masters, Susanne; Bogarín, Diego; Viruel, Juan; van Vugt, Rogier; van Andel, Tinde; de Boer, Hugo J.; Gravendeel, Barbara (Frontiers in Sustainable Food Systems, 2025)
IntroductionEdible terrestrial orchids are endangered worldwide due to overharvesting and illegal trade. One method to distinguish illegally traded wild-collected orchids from sustainably harvested and legally traded cultivated ones is to artificially create hybrids that do not occur naturally and can be morphologically recognized. Creating artificial orchid hybrids is relatively simple. As a result, thousands of artificial orchid hybrids have already been registered with the Royal Horticultural Society, but predominantly for ornamental purposes. We identified a potential hybrid parental pool for edible orchids from terrestrial species that possess desirable traits from both the grower and consumer perspective.MethodFrom the pool of candidate species, we evaluated the possibility of crosses producing viable seed based on phylogenetic distance metrics, based on matK and nrITS sequences of 435 species. Subsequently, we checked the accuracy of our prediction of hybrid compatibility against registered records of hybrids on the International Orchid Register and by experimental production of hybrids.ResultsOur results show that phylogenetic distance can indeed be used as a proxy for predicting hybrid compatibility in orchids.DiscussionPotential of creating edible orchid hybrids for sustainable trade has not yet been fully exploited.